Comparison of Tc-99m GSA scintigraphy and CT volumetry for evaluation in portal vein embolization. Issue 4 (August 2014) - Kono, Yumiko; Kariya, Shuji; Komemushi, Atsushi; Nakatani, Miyuki; Yagi Yoshida, Rie; Suzuki, Satoshi; Ha-Kawa, Sung Kil; Utsunomiya, Keita; Ueno, Yasuhiro; Satoi, Sohei; Kaibori, Masaki; Kon, Masanori; et al.
Abstract Purpose: To determine the correlation of the rate of change of each future remnant liver (FRL) before and after portal vein embolization (PVE), by CT volumetry and Tc-99m galactosyl human serum albumin scintigraphy (GSA scintigraphy). Material and methods: From December 2007 to July 2012, ten patients underwent PVE before hepatic resection. CT volumetry and GSA scintigraphy were performed before and after PVE. The FRL was divided at Cantlie's line for CT volumetry, and volume change rates before and after PVE were calculated. The maximum removal rate (Rmax) was calculated using a radiopharmacokinetic model in GSA scintigraphy. The FRL Rmax change rates before and after PVE were calculated. The correlation between the volume change rates and the Rmax change rates was analyzed. Results: The FRL volume change rate was 1.28 ± 0.26 (mean ± SD); the FRL hypertrophied in all patients significantly (p = 0.005). The FRL Rmax change rate was 1.66 ± 0.75; excluding one patient, there was significant FRL Rmax increase (p = 0.022). Although both increased significantly, no correlation between the volume change rate and the Rmax change rate was observed. Conclusion: No correlation was observed between the FRL volume rate and the Rmax rate.